(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2026)
Plants are sessile organisms that face continuous alterations in environmental conditions. Among such factors, heat stress has been considered one of the most disadvantageous variables to crop productivity. High temperatures rapidly impair photosynthetic efficiency, disturb cellular redox balance, and alter hormonal regulation, hence limiting growth and productivity in plants. Although much literature exists regarding the role of individual protective agents, their combined actions-particularly melatonin and H₂S-have not yet been brought under the spotlight with respect to their ability to improve plant heat tolerance. All the research work carried out in this study was done to investigate physiological, biochemical, hormonal, and molecular responses of plants treated with melatonin and H₂S under heat-stressed conditions. Treatments applied in this experiment were controlled applications of melatonin, H₂S, and their combination, as well as heat stress alone. Among the physiological parameters measured by standard techniques were photosynthetic rate and chlorophyll content. Biochemical responses with regard to ROS accumulation and antioxidant enzyme activities were performed using established assays. In this study, the ABA, IAA, and GA levels were detected by ELISA, and the expressions of heat stress-associated genes HSP70 and HSP90 were determined by qRT-PCR. These results showed that severe heat stress strongly reduced photosynthetic efficiency and chlorophyll content, thereby increasing the accumulation of ROS. Both melatonin and H₂S treatments alone significantly relieved these effects, but combined application was most protective toward photosynthesis, the maintenance of chlorophyll, mitigation of oxidative damage, activation of antioxidant enzymes, and restoration of hormonal balance. Combined treatment also upregulated the transcription of HSP70 and HSP90 strongly, indicating that there is a synergistic molecular mechanism behind improved heat tolerance. In this view, the synergistic use of melatonin and H₂S represents an integrative approach to improved plant tolerance to heat stress by synchronized physiological, biochemical, hormonal, and genetic responses. It could also be highly useful in developing sustainable approaches to the improvement of crop productivity under a globally warming climate.